Inter-Party Insults In Political Discourse In Ghana: A Critical Discourse Analysis - Ofori, Emmanuel Amo (My University, 2018)
In recent times, politics in Ghana has become the politics of personal attack, vilification, and insults. Various attempts have been made to stop this brand of politics, including one spearheaded by the Media Foundation for West Africa, which releases a weekly report to the general public aimed at shaming politicians who are involved in the politics of insults. If a country could go to the extent of shaming politicians involved in politics of insults, then it shows how the issue of intemperate language has become entrenched in Ghanaian political discourse. Thus, there is a need to conduct a thorough analysis of the realization of insults in Ghanaian political discussion. Utilizing a Critical Discourse Analysis approach, this paper analyzes the underlying ideologies in the representation of insults in pro-New Patriotic Party (NPP) and National Democratic Congress (NDC) newspapers. It further compares and contrasts the use of insults in the newspapers.
Keywords: political discourse; Ghana; vilification